Tanggung Jawab Negara terhadap Jaminan Kesehatan dalam Perspektif Hak Asasi Manusia - Fadhillah, Arif; Farizki, Achmad Rassya Nur; Ircham, Hady Hasbiansyah (AHKAM, 2025)
This study examines the state's responsibility in guaranteeing the right to health through the implementation of the National Health Insurance Program (JKN) in Indonesia. Using a normative legal approach, this study analyzes various national and international legal instruments that underlie the state's obligation to provide fair and equitable health services. The results of the study indicate that although JKN has succeeded in expanding access to health, there are still a number of significant challenges, such as service inequality, financing issues, and limited health infrastructure. This study emphasizes the importance of a human rights-based approach in managing JKN, including the principles of non-discrimination, equality, and accessibility. Efforts to improve the efficiency and effectiveness of this program, such as through optimizing technology and increasing the capacity of health workers, are important steps to realizing a sustainable and inclusive national health system. Thus, JKN can be a model for fulfilling the right to better health in the future.